A Percolation-Like Process of Within-Organization Collective Corruption: A Computational Approach. Issue 1 (January 2021) - Kim, Sang-Joon; Lee, Jegoo
This study investigates how collective corruption appears, using a computational method. Specifically, acknowledging that the characteristics of collective corruption process are analogous to percolation phenomena, we illuminate that collective corruption is formed by ongoing social interactions in an organizational boundary. By formulating a percolation-based system dynamics model, we consider the behavioral characteristics of collective corruption in terms of individuals' corruption preferences governed by personal attributes on corruption. We also propose and examine scenarios regarding the formation of collective corruption.